2022
DOI: 10.3389/fsurg.2022.871577
|View full text |Cite
|
Sign up to set email alerts
|

A Simple-To-Use Nomogram for Predicting Early Death in Metastatic Renal Cell Carcinoma: A Population-Based Study

Abstract: BackgroundMetastatic renal cell carcinoma (mRCC) is usually considered to have a poor prognosis, which has a high risk of early death (≤3 months). Our aim was to developed a predictive nomogram for early death of mRCC.MethodsThe SEER database was accessed to obtain the related information of 6,005 mRCC patients between 2010 and 2015. They were randomly divided into primary cohort and validation cohort in radio of 7:3. The optimal cut-off point regarding age at diagnosis and tumor size were identified by the X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The screening process is shown in Figure 1. According to previous studies, early death was defined as death of patients within 3 months of diagnosis (13)(14)(15). All the included patients with mCRC were divided into a training cohort (accounting for 70%) and a validation cohort (accounting for 30%).…”
Section: Introductionmentioning
confidence: 99%
“…The screening process is shown in Figure 1. According to previous studies, early death was defined as death of patients within 3 months of diagnosis (13)(14)(15). All the included patients with mCRC were divided into a training cohort (accounting for 70%) and a validation cohort (accounting for 30%).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the International Classification of Diseases for Oncology, 3rd Edition, lung cancer was classified as adenocarcinoma, squamous cell carcinoma (SCC), small cell lung cancer (SCLC), large cell lung cancer (LCLC), and nonsmall cell lung cancer or not otherwise specified lung cancer (NSCLC/NOS). The variables were extracted from the SEER plan, including age, gender, race, marital status, histological type, tumor grade, primary site, laterality, tumor size, TNM stage, distant metastasis, surgery (Code 12,13,15,(19)(20)(21)(22)(23)(24)(25)30,33,45,46,55,56,65,66,80,90), radiotherapy and chemotherapy. The following inclusion criteria were applied (1): diagnosed from 2011 to 2015 (2); lung cancer is the only malignant tumor (3); primary diagnosed lung cancer patients with BM.…”
Section: Patient Cohortsmentioning
confidence: 99%
“…Nomograms, as a visual statistical tool, can integrate multiple variables to predict the individual prognosis (15). Compared to conventional staging systems, nomograms facilitate clinical decision-making with increased accuracy and more intuitive prognostic assessment (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple body indicators (including balance) can predict death and improve the performance of prediction models ( 10 ). Previous studies showed age and diabetes were indicators for death ( 11 , 12 ). The Short Physical Performance Battery (SPPB) ( 13 ) is one of the most effective tools for assessing this, but how balance ability indicates all-cause death in middle-aged and old Chinese adults with overweight and obesity has not been studied.…”
Section: Introductionmentioning
confidence: 99%